On super edge-magic total labelings of a forest of banana trees - Ahmad, Ali,; Ali, Kashif,; Baskoro E.T., (Utilitas Mathematica, 2010)
An edge-magic total labeling on a graph with v vertices and e edges is defined as a one-to-one mapping taking the vertices and edges of graph onto the integers 1,2,..., v + e with the property that the sum of the label of an edge and the labels of its endpoints is a constant independent of the choice of the edge. This paper is devoted to determine super edge-magic total labelings for a subdivision of a banana tree and a disjoint union of banana trees.